Wastewater treatment : biological and chemical processes. - Henze, Mogens, 1945-; Harremoës, Poul, ....-; la Cour Jansen, Jes, ....- (Berlin : Springer, 2002)
This book gives a most detailed presentation of the theories behind modern wastewater treatment processes. It presents an up-to-date description of wastewater characteristics and the theories of biological processes and their modelling. The quantitative information density is unique due to the numerous tables, figures and examples.The book is primarily intended for graduate and PhD students, but owing to the abundant quantitative information it is also valuable for consulting engineers and other professionals who deal with wastewater treatment. The book has an extensive Table of Contents and list of symbols, which makes it useful as a handbook.
Keywords: Afvalwaterzuivering